The Accelerating Change in Medical Education Consortium: Key Drivers of Transformative Change. (July 2021) - Lomis, Kimberly D.; Santen, Sally A.; Dekhtyar, Michael; Elliott, Victoria Stagg; Richardson, Judee; Hammoud, Maya M.; Hawkins, Richard; Skochelak, Susan E.
Abstract : The American Medical Association's (AMA's) Accelerating Change in Medical Education (ACE) initiative, launched in 2013 to foster advancements in undergraduate medical education, has led to the development and scaling of innovations influencing the full continuum of medical training. Initial grants of $1 million were awarded to 11 U.S. medical schools, with 21 schools joining the consortium in 2016 at a lower funding level. Almost one-fifth of all U.S. MD- and DO-granting medical schools are represented in the 32-member consortium. In the first 5 years, the consortium medical schools have delivered innovative educational experiences to approximately 19, 000 medical students, who will provide a potential 33 million patient care visits annually. The core initiative objectives focus on competency-based approaches to medical education and individualized pathways for students, training in health systems science, and enhancing the learning environment. At the close of the initial 5-year grant period, AMA leadership sought to catalogue outputs and understand how the structure of the consortium may have influenced its outcomes. Themes from qualitative analysis of stakeholder interviews as well as other sources of evidence aligned with the 4 elements of the transformational leadership model (inspirational motivation, intellectual stimulation, individualized consideration, and idealized influence) and can be used to inform future innovation interventions. For example, the ACE initiative has been successful in stimulating change at the consortium schools and propagating those innovations broadly, with outputs involving medical students, faculty, medical schools, affiliated health systems, and the broader educational landscape. In summary, the ACE initiative has fostered a far-reaching community of innovation that will continue to drive change across the continuum of medical education.